Alfalfa MsbHLH115 confers tolerance to cadmium stress through activating the iron deficiency response in Arabidopsis thaliana - Zhang, Miao; Gao, Jing-Yun; Dong, Shi-Chen; Chang, Meng-Han; Zhu, Jing-Xuan; Guo, Dong-Lin; Guo, Chang-Hong; Bi, Ying-Dong (Frontiers in Plant Science, 2024)
Cadmium (Cd) pollution severely affects plant growth and development, posing risks to human health throughout the food chain. Improved iron (Fe) nutrients could mitigate Cd toxicity in plants, but the regulatory network involving Cd and Fe interplay remains unresolved. Here, a transcription factor gene of alfalfa, MsbHLH115 was verified to respond to iron deficiency and Cd stress. Overexpression of MsbHLH115 enhanced tolerance to Cd stress, showing better growth and less ROS accumulation in Arabidopsis thaliana. Overexpression of MsbHLH115 significantly enhanced Fe and Zn accumulation and did not affect Cd, Mn, and Cu concentration in Arabidopsis. Further investigations revealed that MsbHLH115 up-regulated iron homeostasis regulation genes, ROS-related genes, and metal chelation and detoxification genes, contributing to attenuating Cd toxicity. Y1H, EMSA, and LUC assays confirmed the physical interaction between MsbHLH115 and E-box, which is present in the promoter regions of most of the above-mentioned iron homeostasis regulatory genes. The transient expression experiment showed that MsbHLH115 interacted with MsbHLH121pro. The results suggest that MsbHLH115 may directly regulate the iron-deficiency response system and indirectly regulate the metal detoxification response mechanism, thereby enhancing plant Cd tolerance. In summary, enhancing iron accumulation through transcription factor regulation holds promise for improving plant tolerance to Cd toxicity, and MsbHLH115 is a potential candidate for addressing Cd toxicity issues.